The Morphogenesis and Growing Properties of Valeriana officinalis L. (Experimental biology, 2016)
Valeriana officinalis L. - is not found species in the wild in the flora of Kazakhstan. Homeland V. officinalis is Mediterranean. The species is also common in the subtropics and temperate climate zones. It is found in Europe, Central Asia and it’s the northern part, in North America and South America. Typically plant grows along the banks of rivers and floodplains, found in the exposition of hillsides, swamps and forests. Often the underground part of the plant forms a tuberous thickening at the expense of sprawl parenchyma cells of the roots cortex. Learning plant species recently have great demand as a medicinal. The preform feedstock of this type can only result in the creation of artificial plantations. In connection with this there is a need in Kazakhstan introduction of the species in culture.The article describes morphogenesis, growth and development valerian under experimental conditions and in culture. They’re provides information about the features of ontogenesis of the test species, different life stages (latent, virginal, juvenile and generative). In accordance with the ontogenetic characteristics of valerian have been given advice.  We should take into account the climatic and physical geographical characteristics of southern Kazakhstan. Optimal for full growth and development of plants soil type, crop rotation culture were found. The best precursor for valerian – species of Poacea or  fodder crops. Due to the decline in the quality of root exudates in the soil, we recommend planting this crop legume after the second year. For good growth and development of valerian is required mechanically loose soil.  Discussed farming practices for the proper growth and development of the studied species. Within the Southern Kazakhstan the most appropriate method of reproduction dosage of species valerian is a preparation of seedlings. At pushed plot area (1m2, aisles - 10-12 cm) is required 1.5-2.0 g of seeds. Land planted with top cover manure 1-1.5 cm thick. On 1 hectare of seedlings required 100-150 m2 pushed plot sites. The сare object- species of valerian involves maintaining a constant humidity of the soil (6-8 one-time watering). For full plant (Valeriana officinalis) growth requires that the site was free of weeds; loosens not less than 2 times and has received an additional fertilizer. More effective to plant seedlings of Valeriana officinalis on a medium (70 x 20 cm or 70 x 25 cm) in autumn (the second half of October) or early spring. Seeds are sown in early August. V. officinalis L. is actively growing and fruiting, giving viable seeds; responsive to culture conditions and gives self-seeding.
Keywords: flora of Kazakhstan; morphogenesis; ontogenesis; productivity; a medicinal plant